Students’ Informal Learning Practices and Social Interaction in a University Library: A Qualitative Case Study - Star Level Rambe; Faisal Riza (Jurnal IPTEK Bagi Masyarakat, 2026)
University libraries can support individual study as well as informal interaction, but evidence from a single setting should not be used to infer an institutional transformation. This study examines how students describe and enact “intellectual hangout” practices at the Library of Universitas Pembangunan Panca Budi. A qualitative case study design was used. Data were drawn from observation, interviews with 12 students and 2 librarians, and documentation. The available data show that participants combined social interaction with academic activities, particularly assignment discussions, collaborative work, information exchange, internet use, and computer use. Students also described the library as relatively comfortable and conducive to focusing. These findings indicate observed academic-social practices and several characteristics associated with an informal learning space and, more cautiously, a third place. However, the study does not establish that the library has fully transformed into a third place or that these activities improve academic performance. Practical implications concern zoning, flexible collaborative areas, digital access, and routine user-feedback mechanisms.